2019
DOI: 10.5812/aapm.96117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transforaminal Triamcinolone and Dexmedetomidine in Radicular Low-Back Pain

Abstract: BackgroundAdministration of steroids in the lumbar transforaminal block for lumbar radicular pain is considered one of the preferred treatment methods though it is associated with some complications. ObjectivesThe effects and side effects of triamcinolone and dexmedetomidine in the lumbar transforaminal block were investigated in the present study.MethodsIn this study, 30 patients, aged 40 - 70 years, suffering from lumbar radicular pain arising from the lumbar disc protrusion were equally divided into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Dexmedetomidine is a very interesting drug with many indications and effects in the form of analgesia and sedation. Moreover, it has proven to be an effective additive in many studies and through many routes (14)(15)(16). These characteristics are attributed to its mechanism of action as it works as an alpha-1 receptor agonist, which has sedative and analgesic effects with the advantage of no respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a very interesting drug with many indications and effects in the form of analgesia and sedation. Moreover, it has proven to be an effective additive in many studies and through many routes (14)(15)(16). These characteristics are attributed to its mechanism of action as it works as an alpha-1 receptor agonist, which has sedative and analgesic effects with the advantage of no respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed that several factors such as the injection approach (19), type of anesthetic (24,25), the number of injections (26), and type and dose of steroids could be different from study to study (27). Therefore, such differences should be kept in mind when comparing the results of different investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have studied adjuvants that increase the duration of analgesia while simultaneously maintaining a safe side effect profile (8)(9)(10). The most commonly employed agents are perineural dexamethasone and dexmedetomidine (11)(12)(13). Our study evalu-Copyright © 2021, Author(s).…”
Section: Introductionmentioning
confidence: 99%